A novel self-powered MR damper: theoretical and experimental analysis. (23rd September 2015) - Xinchun, Guan; Yonghu, Huang; Yi, Ru; Hui, Li; Jinping, Ou
Abstract: This paper presents a novel magnetorheological (MR) damper with a self-powered capability, which is proposed to have energy harvesting and MR damping technologies integrated into a single device. Vibration energy harvesting mechanisms were adopted, based on ball-screw mechanisms and a rotary permanent magnet dc generator, to convert the external vibration energy into electrical energy to power the MR damping unit. The configuration and operating principles of the proposed self-powered MR damper were presented. Considering the core loss effect on the magnetic field, a theoretical analysis of the proposed MR damper was carried out and a mechanical model was developed. Finally, a prototype with a capacity of 10 kN was fabricated and experimentally investigated in both the direct-supply mode and the supply-with-rectifier mode. The results indicated that the proposed configuration is feasible and that both modes can realize good self-adaptability of the MR damping force. However, the direct-supply mode has a sag effect in the force–displacement curve and provides a lower energy-dissipating capacity than the direct-supply mode does under the same conditions.